Substituição de amido de mandioca por amido de araruta e de arroz em pão de queijo congelado - Papalia, Índira da Silva (2017)
Market growth for cheese bread has reached new trends, such as the freezing process and mixtures with addition of new starches. The technological characteristics and new applications of arrowroot starch and rice in relation to their viscosity properties have been extensively studied for baking products, as possibility substitution other sources of commonly used starch such as cassava starch in the production of bread cheese. The objective of the present work was to evaluate the physical-chemical characteristics and texture of cheese bread adopting the rice starch (x1), cassava (x2) and arrowroot (x3) simplex-centroid design yielding 9 treatments with 2 replicates at the central point. The optimum formulation was evaluated for physical-chemical characteristics, texture and sensory acceptance. The study also involved evaluating the physical-chemical and texture characteristics during the 180 days of commercial freezing storage. The optimized formulation was defined considering simultaneously texture and physico-chemical characteristics and resulted in mixing with 18% rice starch, 72% arrowroot starch and 10% cassava starch. The optimized cheese bread formulation presented all physical-chemical and texture characteristics within the confidence interval (CI 95%) determined by the models, except the protein and lipid content that estimated the linear model and these are related to the composition of the ingredients. The sensory acceptance of the optimized cheese bread presented an average of 7.93 for appearance, 7.76 for aroma, 7.67 for flavor and 7.37 for texture. For the overall impression the tasters attributed 7.75, that is, the optimized formulation showed good acceptance even though the tasters realized that the texture of the cheese bread was hard than desired. The cheese breads made with cassava starch and the ternary mixture with starches showed a loss of moisture during the 180 days of storage. All the mixtures presented a reduction in hardness and chewiness of the cheese bread over the storage time. The present study allowed the conclusion that it is possible to obtain cheese bread with substitution of up to 90% of cassava starch, using rice starch and arrowroot. Although it is necessary to adjust the proportions of the last two starches with the objective of improving the texture and appearance of cheese bread.